Fireproof plugging material, preparation method and application thereof
Patent Information
- Application Number
- CN202611444364.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-10-23
AI Technical Summary
[0003]然而,上述无机填料主要以物理分散状态存在于硅橡胶基体中,材料受火裂解并发生体积收缩时,容易出现界面分离、填料团聚以及裂纹扩展等问题
[0024]根据本申请,所述防火封堵材料在固化成型后具有稳定的形状和尺寸,并具有一定的柔韧性、力学强度和耐高温性能,可根据贯穿孔口、电缆桥架或管道的布置形式,通过模具制成不同形状和尺寸的防火封堵模块。由此,可将材料的混合、脱泡、成型和热固化过程集中在生产阶段完成,减少施工现场的操作步骤,便于防火封堵模块的标准化生产、运输、拼装和更换。在模块受火过程中,硼硅氧烷改性剂能够促进硅橡胶受热残余物与陶瓷化填料之间的高温黏结和固结,减少烧后残余物的松散、粉化和脱落;改性硅灰石则能够进一步调节含硼体系的高温烧结过程,降低过度烧结和体积收缩倾向,并使硼硅氧烷改性剂的高温黏结作用更加有利于残余骨架的稳定连接和固结。二者配合后,有利于降低防火封堵模块受火后的线收缩和开裂,提高烧后残余强度、外形保持能力以及封堵连续性。因此,采用所述防火封堵材料制备防火封堵模块,能够减少模块自身以及相邻模块之间因高温收缩、开裂产生贯通缝隙的风险,提高贯穿孔口防火封堵结构受火后的整体稳定性和可靠性。
Smart Images

Figure CN122958876A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of fireproof sealing materials technology, specifically to a fireproof sealing material, its preparation method, and its application. Background Technology
[0002] Fire-stopping materials are mainly used for fireproofing building openings, cable trays, and pipe penetrations. Silicone rubber possesses properties such as high and low temperature resistance, flexibility, weather resistance, and insulation, making it suitable as a matrix for fire-stopping materials. Existing silicone rubber-based fire-stopping materials typically improve their flame-retardant and high-temperature ceramization properties by adding flame-retardant fillers such as aluminum hydroxide and magnesium hydroxide, as well as ceramic fillers such as mica powder, wollastonite, and glass powder.
[0003] However, the aforementioned inorganic fillers mainly exist in a physically dispersed state within the silicone rubber matrix. When the material is subjected to fire cracking and volume shrinkage, problems such as interface separation, filler agglomeration, and crack propagation easily occur. Although existing boron-containing components can promote the softening, bonding, and sintering of silicon-oxygen residues, they lack stable connections with the silicone rubber crosslinking network and are prone to migration or local enrichment when heated. Although MQ silicone resin can improve crosslinking density and high-temperature residue, the silicon-oxygen-rich residual skeleton it forms may still crack due to shrinkage and embrittlement.
[0004] Therefore, existing silicone rubber-based fire-stopping materials still struggle to simultaneously address the dispersion stability of boron-containing components, the interfacial bonding between various inorganic residues, and sintering densification. This results in the ablation layer of the material after exposure to fire being prone to shrinkage cracking, pulverization, or localized detachment. Improving the continuity of the high-temperature residual structure, crack resistance, and overall structural integrity of the material is a pressing technical problem that needs to be solved in this field. Summary of the Invention
[0005] This application provides a fire-resistant sealing material, its preparation method, and its application. By introducing hydrogen-containing MQ silicone resin, borosilicate modifier, and alumina sol-modified wollastonite into a vinyl polysiloxane system, the borosilicate modifier promotes high-temperature bonding and consolidation between post-firing residues, while the modified wollastonite stabilizes the inorganic framework and regulates the sintering behavior of the boron-containing high-temperature phase, thereby reducing excessive shrinkage and cracking. Simultaneously, the borosilicate modifier participates in the hydrosilylation reaction, improving its bonding stability within the material. This reduces post-firing linear shrinkage, minimizes cracking, pulverization, and flaking, and improves post-firing residual strength and structural integrity.
[0006] In a first aspect, this application provides a fire-stopping material comprising the following raw materials in parts by weight: 100 parts vinyl polysiloxane, 8-16 parts hydrogen-containing MQ silicone resin, 4-8 parts borosilicate modifier, 4-8 parts modified wollastonite, 20-35 parts flame retardant filler, 30-40 parts ceramicized filler, 6-12 parts reinforcing filler, 0.2-0.6 parts platinum catalyst and 0.05-0.1 parts inhibitor; The borosilicate modifier is prepared by a condensation reaction of hydroxyl-terminated polysiloxane, trialkyl borate, and vinylalkoxysilane. The modified wollastonite is obtained by modifying wollastonite with alumina sol.
[0007] According to this application, vinyl polysiloxane serves as the matrix material, providing the fire-resistant sealing material with molding and processing properties, flexibility, and basic mechanical properties; hydrogen-containing MQ silicone resin participates in hydrosilylation crosslinking and improves the shape stability of the material after curing and the amount of silicon-rich oxygen residue after exposure to fire; flame-retardant fillers are used to inhibit the combustion of the material and reduce flame spread; ceramicized fillers are used to increase the amount of residue after exposure to fire and participate in the formation and consolidation of the residue skeleton under high temperature conditions; reinforcing fillers are used to improve the processing stability of the material before curing and the mechanical properties after curing.
[0008] To address the issues of cracking, powdering, and localized detachment in existing fire-resistant sealing materials during continuous heating and volume shrinkage, simply increasing the amount of inorganic filler not only fails to effectively improve the bonding between residues but also easily leads to increased viscosity and decreased molding performance. Therefore, this application first introduces a borosilicate modifier. The borosilicate-containing structure formed after firing promotes the softening, bonding, and sintering consolidation between the silica-rich residues and the ceramicized filler, enabling the high-temperature residues added by the hydrogen-containing MQ silicone resin to be more effectively transformed into a continuous, load-bearing post-firing structure. The borosilicate modifier used in this application is not a common boron-containing sintering aid but is prepared by a condensation reaction of hydroxyl-terminated polysiloxane, trialkyl borate, and vinylalkoxysilane, resulting in a modifier that simultaneously contains polysiloxane segments, a Si-OB structure, and reactive vinyl groups. Polysiloxane segments facilitate the compatibility and stable distribution of modifiers in the organosilicon matrix. The Si-OB structure provides high-temperature softening, bonding, and sintering promotion after firing. Vinyl groups can undergo hydrosilylation reactions with Si-H in hydrogen-containing MQ silicone resin during the material curing process, allowing borosilicate modifiers to participate in the curing network. This reduces the possibility of migration, precipitation, and local enrichment of ordinary boron-containing components during mixing, molding, and heating, thus enabling their high-temperature bonding effect to be more stable and uniform.
[0009] However, during further optimization, this application discovered that the effect of borosilicate modifiers does not continuously increase with increasing dosage. When the boron-containing softening phase increases to a certain extent, although the wetting and bonding abilities between residues further improve, it is also prone to accompanied by significant sintering densification, localized flow, and volume shrinkage, leading to a new performance contradiction in the material: "enhanced bonding but simultaneously increased shrinkage." Especially in thicker fire-retardant modules, different regions exhibit varying degrees of heating and softening. Excessive boron-containing softening can lead to inconsistent local structural rearrangement and shrinkage. Therefore, simply increasing the dosage of borosilicate modifiers is insufficient to achieve lower post-firing shrinkage and higher residual strength. To address this new problem arising from the introduction of borosilicate modifiers, this application further introduces modified wollastonite obtained through alumina sol treatment. This allows the aluminum-containing components in the alumina sol to preferentially adhere to and distribute on the wollastonite surface. After subsequent drying and heat treatment, an aluminum-rich surface structure is formed, which is used to regulate the high-temperature sintering behavior of the boron-containing system and improve the stability of the residual skeleton.
[0010] After alumina sol is pre-attached and heat-treated to form on the surface of wollastonite, the alumina-rich components maintain a relatively tight spatial bond with the wollastonite particles that actually participate in the post-firing skeleton construction. During the firing process, the modified wollastonite can, on the one hand, improve the structural retention ability of the inorganic skeleton in the presence of boron-containing softening phases, and reduce the tendency for excessive densification and volume shrinkage after the enhancement effect of borosilicates. On the other hand, the alumina-rich components on the modified wollastonite surface may participate in the formation and sintering process of the boron-containing high-temperature phase, thereby regulating the softening degree, fluidity, and sintering behavior of the boron-containing high-temperature phase. Combining the test results of post-firing linear shrinkage, maximum crack width, and post-firing residual compressive strength, it can be considered that the above-mentioned alumina-rich surface structure is beneficial to reducing the volume shrinkage caused by excessive flow and rapid densification of the boron-containing softening phase, and allows the high-temperature bonding effect of the borosilicate modifier to be used more for the connection and consolidation between the residual skeletons. Therefore, modified wollastonite not only eliminates the shrinkage side effects caused by further use of borosilicate modifiers, but also improves the effectiveness of the same amount of borosilicate modifier in enhancing the residual structure after firing.
[0011] Furthermore, when borosilicate modifiers are used alone, they can improve the high-temperature bonding and consolidation between residues. However, once their effect is enhanced to a certain extent, they are prone to excessive sintering and shrinkage. The addition of modified wollastonite can regulate the degree of high-temperature sintering, allowing the boron-containing binder phase formed by borosilicates to be used more extensively to connect and fix the stable inorganic framework. Therefore, with the same amount of borosilicate modifier, lower post-firing linear shrinkage and crack width, as well as higher post-firing residual strength, can be obtained. Conversely, while modified wollastonite alone can improve the high-temperature stability of the residual framework, it still lacks sufficient continuous bonding and consolidation between particles, limiting its improvement on post-firing residual strength. Borosilicate modifiers can further connect modified wollastonite, silica-rich residues, and other ceramicized fillers into a whole, ultimately transforming the framework stabilization effect of modified wollastonite into higher post-firing structural strength.
[0012] In some embodiments, the preparation method of the borosilicate modifier includes the following steps: 100 parts of hydroxyl-terminated polysiloxane, 4-10 parts of trialkyl borate, and 5-12 parts of vinylalkoxysilane were mixed and reacted at 70-90°C for 1.5-3 hours under anhydrous and nitrogen protection to induce a condensation reaction between the hydroxyl-terminated polysiloxane, trialkyl borate, and vinylalkoxysilane. Subsequently, the temperature was raised to 110-130°C and the reaction was continued for 1-2 hours under a pressure of 4-10 kPa. The low-molecular-weight substances generated in the reaction were removed to obtain a product containing polysiloxane segments, Si-OB structure, and vinyl groups, which was used as a borosilicate modifier.
[0013] In some of the aforementioned methods, the Si-OH groups in hydroxyl-terminated polysiloxanes can undergo condensation reactions with the B-OR groups in trialkyl borate esters and the Si-OR groups in vinylalkoxysilanes, respectively, to form Si-OB bonds and Si-O-Si bonds, releasing the corresponding low-molecular-weight alcohols. By controlling the amounts of trialkyl borate esters and vinylalkoxysilanes, the resulting product retains the polysiloxane segments while introducing appropriate amounts of Si-OB structures and vinyl groups. This avoids excessive condensation leading to high viscosity or gelation, and allows the vinyl groups to undergo hydrosilylation reactions with the Si-H groups in hydrogen-containing MQ silicone resins during subsequent curing. This results in a borosilicate modifier that combines high-temperature sintering promotion and crosslinking reactivity.
[0014] In some embodiments, the hydroxyl-terminated polysiloxane is a hydroxyl-terminated polydimethylsiloxane, the viscosity of which at 25°C is 1000–2000 mPa·s, the trialkyl borate includes at least one of trimethyl borate, triethyl borate, and triisopropyl borate, and the vinylalkoxysilane includes at least one of vinyltrimethoxysilane and vinyltriethoxysilane.
[0015] In some embodiments, the method for preparing the modified wollastonite includes the following steps: 100 parts of wollastonite were dispersed in water, and 15-40 parts of alumina sol were added at 50-70°C with stirring. The mixture was continued for 30-60 minutes to allow the alumina sol to adhere to the surface of the wollastonite. The wollastonite was then dried at 100-120°C for 1-2 hours, followed by heat treatment at 250-350°C for 0.5-2 hours. After cooling, the wollastonite was sieved to obtain the modified wollastonite. The solid content of the alumina sol is 15-25 wt%.
[0016] In some embodiments, the vinyl polysiloxane is a vinyl-terminated polydimethylsiloxane, wherein the vinyl-terminated polydimethylsiloxane has a viscosity of 3000-8000 mPa·s at 25°C and a vinyl content of 0.20-0.50 wt%.
[0017] In some embodiments, the molar ratio of M structural units to Q structural units in the hydrogen-containing MQ silicone resin is 0.7 to 1.1:1, the Si-H content is 0.10 to 0.30 wt%, and the number-average molecular weight is 2000 to 6000.
[0018] In some embodiments, the flame-retardant filler is one or more of aluminum hydroxide, magnesium hydroxide, and zinc borate.
[0019] In some embodiments, the ceramicized filler is one or more of mica powder, wollastonite, and glass powder.
[0020] In some embodiments, the reinforcing filler is at least one of fumed silica and precipitated silica.
[0021] Secondly, this application provides a method for preparing a fire-resistant sealing material, comprising the following steps: S1. Provide the raw materials included in the fire-stopping material according to any embodiment of the first aspect; S2. Mix vinyl polysiloxane, borosilicate modifier, modified wollastonite, flame retardant filler, ceramicized filler and reinforcing filler evenly to obtain the base adhesive; S3. The base adhesive is divided into two parts. One part of the base adhesive is mixed with a platinum catalyst to obtain the first component. The other part of the base adhesive is mixed with hydrogen-containing MQ silicone resin and an inhibitor to obtain the second component. S4. The first component and the second component are mixed to allow the Si-H in the hydrogen-containing MQ silicone resin to undergo a hydrosilylation reaction with the vinyl polysiloxane and the vinyl in the borosilicate modifier, and the fireproof sealing material is obtained after curing.
[0022] According to the preparation method of this application, vinyl polysiloxane, borosilicate modifier, modified wollastonite, and various fillers are first mixed to form a base adhesive. This allows the borosilicate modifier and modified wollastonite to be fully dispersed in the same system before the curing reaction, which is beneficial for their synergistic effect during subsequent firing. Specifically, the modified wollastonite can regulate the softening, flow, and sintering process of the boron-containing high-temperature phase formed by the borosilicate modifier, making the high-temperature bonding effect of the borosilicate modifier more conducive to the connection and consolidation of the residual skeleton, thereby reducing over-sintering and volume shrinkage, and improving the post-firing structural stability. The base adhesive was then divided into two parts, with the platinum catalyst, hydrogen-containing MQ silicone resin, and inhibitor added to different parts respectively. This reduces the risk of premature contact between the two components during mixing and storage, which could lead to localized rapid reactions. When the first and second components were finally mixed, the Si-H in the hydrogen-containing MQ silicone resin could undergo hydrosilylation reactions with the vinyl groups in the vinyl polysiloxane and borosilicate modifier, forming a more uniform curing network while ensuring the stable retention of the borosilicate modifier within the system. This preparation method, which involves first fully dispersing the borosilicate modifier and modified wollastonite before grouping and curing, effectively balances the material's curing stability with low shrinkage, crack resistance, and residual strength after exposure to heat.
[0023] Thirdly, this application provides the application of the fire-stopping material described in any embodiment of the first aspect or the fire-stopping material prepared by the preparation method described in the second aspect in the preparation of fire-stopping modules.
[0024] According to this application, the fireproof sealing material, after curing, has a stable shape and size, and possesses certain flexibility, mechanical strength, and high-temperature resistance. It can be molded into fireproof sealing modules of different shapes and sizes according to the arrangement of through-holes, cable trays, or pipes. This allows the mixing, degassing, molding, and thermosetting processes of the material to be completed in the production stage, reducing on-site operational steps and facilitating standardized production, transportation, assembly, and replacement of the fireproof sealing modules. During the fire exposure process, the borosilicate modifier promotes high-temperature bonding and consolidation between the heated silicone rubber residue and the ceramicized filler, reducing the loosening, pulverization, and detachment of the residue after burning. Modified wollastonite further regulates the high-temperature sintering process of the boron-containing system, reducing over-sintering and volume shrinkage tendencies, and making the high-temperature bonding effect of the borosilicate modifier more conducive to the stable connection and consolidation of the residual skeleton. The combination of these two factors helps reduce linear shrinkage and cracking of the fireproof sealing module after fire exposure, improving post-fire residual strength, shape retention, and sealing continuity. Therefore, using the aforementioned fireproof sealing material to prepare fireproof sealing modules can reduce the risk of through gaps caused by high-temperature shrinkage and cracking of the module itself and adjacent modules, and improve the overall stability and reliability of the fireproof sealing structure of the through hole after being exposed to fire.
[0025] Compared with the prior art, the beneficial effects of this application are at least as follows: 1. This application utilizes a combination of borosilicate modifier and modified wollastonite. Building upon the borosilicate modifier's role in promoting high-temperature bonding and consolidation of post-firing residues, the modified wollastonite further regulates the high-temperature sintering process of the boron-containing system, reducing over-sintering and volume shrinkage that can easily occur after the enhanced effect of borosilicate. Simultaneously, the modified wollastonite helps to more fully transform the high-temperature bonding effect of borosilicate into the connection and consolidation of the residual framework, thereby further reducing post-firing shrinkage and cracking, and improving post-firing residual strength and overall structural integrity.
[0026] 2. This application first prepares a base adhesive, then adds a platinum catalyst and hydrogen-containing MQ silicone resin to different portions of the adhesive, and finally mixes and cures them. This facilitates uniform dispersion of the raw materials and reduces localized gelation and uneven curing caused by premature reaction. The resulting fire-resistant sealing material exhibits good molding and dimensional stability, and can reduce shrinkage, cracking, powdering, and localized detachment after exposure to fire, while improving residual strength and shape retention after burning. It is suitable for manufacturing fire-resistant sealing modules. Attached Figure Description
[0027] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0028] Figure 1 The image shows the infrared spectrum of the borosilicate modifier. Detailed Implementation
[0029] The various embodiments or implementation schemes in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments.
[0030] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with an embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0031] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0032] In this specification, unless otherwise specified, "parts" refers to "parts by weight".
[0033] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0034] Vinyl polysiloxane: Vinyl-terminated polydimethylsiloxane, with a viscosity of 5000 mPa·s at 25°C and a vinyl content of 0.30 wt%; Hydrogen-containing MQ silicone resin: Solvent-free hydrogen-containing MQ silicone resin, wherein the molar ratio of M structural units to Q structural units is 0.90:1, the Si-H content is 0.20wt%, and the number average molecular weight is 4000; Hydroxyl-terminated polysiloxane: Hydroxyl-terminated polydimethylsiloxane, with a viscosity of 1500 mPa·s at 25°C and a hydroxyl content of 0.50 wt%; Trialkyl borate: Triethyl borate, purity 99.0 wt%; Vinylalkoxysilane is vinyltrimethoxysilane, purity 98.0 wt%, vinyl content 18.2 wt%; Wollastonite: acicular wollastonite with a median grain size D50 of 15 μm and an aspect ratio of 10:1; Alumina sol: Neutral alumina sol was used, with an average particle size of 10 nm and a solid content of 20 wt%. Flame-retardant filler: composed of aluminum hydroxide and zinc borate in a mass ratio of 5:1. The median particle size D50 of both aluminum hydroxide and zinc borate can be controlled to approximately 5 μm. Ceramicized filler: Composed of mica powder, wollastonite, and glass powder in a mass ratio of 6:4:5. Specifically, the mica powder is white mica powder with a median particle size (D50) of 18 μm and an aspect ratio of 30:1; the wollastonite is acicular wollastonite with a median particle size (D50) of 15 μm and an aspect ratio of 10:1; and the glass powder is low-melting-point glass powder with a median particle size (D50) of 10 μm and a softening temperature of 520℃. Reinforcing filler: Fumed silica with a specific surface area of 200 m² 2 / g, with a native particle size of 12nm; Catalyst: Karstedt platinum catalyst was used; Inhibitor: 1-ethynyl-1-cyclohexanol with a purity of 99.0 wt% was used.
[0035] Preparation Example 1 Preparation of borosilicate modifiers: 100 parts of hydroxyl-terminated polydimethylsiloxane, 7 parts of triethyl borate, and 8 parts of vinyltrimethoxysilane were added to a dry reaction vessel. The mixture was stirred at 300 r / min under nitrogen protection and heated to 80 °C for 2 h. The temperature was then increased to 120 °C, and the absolute pressure inside the reaction vessel was adjusted to 6 kPa. The reaction was continued for 1.5 h to remove ethanol, methanol, and unreacted low-molecular-weight substances generated during the reaction. After the reaction was completed, the mixture was cooled to room temperature under nitrogen protection to obtain a borosilicate modifier.
[0036] from Figure 1 It can be seen that the obtained borosilicate modifier has a viscosity of 3400–3500 cm⁻¹ -1 The presence of a broad hydroxyl absorption peak at 2900–3000 cm⁻¹ indicates the presence of a small amount of unreacted Si-OH or adsorbed water in the system; -1 The absorption peak at approximately 1600 cm⁻¹ is attributed to the stretching vibration of CH in Si-CH₃, indicating that the polydimethylsiloxane segments are retained. -1 The characteristic absorption peak of vinyl C=C appears at approximately 895 cm⁻¹, indicating that the unsaturated double bond of vinyltrimethoxysilane was not consumed after its introduction, and can provide an active site for subsequent hydrosilylation reaction with Si-H groups. -1 and 670cm -1Characteristic absorptions of the Si-OB / BO-Si structure were observed nearby, indicating that boron has been introduced into the siloxane system via a condensation reaction; approximately 1090 cm⁻¹ -1 There is a strong Si-O-Si stretching vibration absorption peak at approximately 800 cm⁻¹. -1 The absorption at this point is characteristic of Si-CH3 and the siloxane backbone. The simultaneous presence of these characteristic peaks, and the significantly weaker absorption of the hydroxyl group compared to the terminal hydroxyl polysiloxane, indicates that the terminal hydroxyl polysiloxane underwent condensation reactions with triethyl borate and vinyltrimethoxysilane, respectively, forming Si-OB and Si-O-Si structures while retaining the polysiloxane backbone and vinyl activity. This suggests that the chemical structure of the resulting product is essentially consistent with the expected borosilicate modifier.
[0037] Preparation Example 2 Preparation of modified wollastonite: 100 parts of wollastonite were dispersed in deionized water to form a wollastonite suspension with a solid content of 30 wt%. The suspension was heated to 60°C, and 25 parts of neutral alumina sol with a solid content of 20 wt% were slowly added under stirring. The mixture was stirred for 45 min to allow the alumina sol to fully adhere to the surface of the wollastonite. The mixture was then filtered, dried at 110°C for 1.5 h, and then heat-treated at 300°C for 1 h. After cooling, depolymerization, and sieving, modified wollastonite was obtained.
[0038] Comparative Preparation Example 1 Preparation of borosilicate modifiers: 100 parts of hydroxyl-terminated polydimethylsiloxane, 7 parts of triethyl borate, and 7.35 parts of methyltrimethoxysilane (equally replacing 8 parts of vinyltrimethoxysilane) were added to a dry reaction vessel. The mixture was stirred at 300 rpm under nitrogen protection and heated to 80°C for 2 hours. The temperature was then increased to 120°C, and the absolute pressure inside the reaction vessel was adjusted to 6 kPa. The reaction continued for 1.5 hours to remove low-molecular-weight substances generated during the reaction. After the reaction was complete, the mixture was cooled to room temperature under nitrogen protection to obtain a borosilicate modifier free of reactive vinyl groups.
[0039] Comparative Preparation Example 2 Preparation of silica sol-modified wollastonite: 100 parts of wollastonite were dispersed in deionized water to form a wollastonite suspension with a solid content of 30 wt%. The suspension was heated to 60°C, and 25 parts of neutral silica sol with a solid content of 20 wt% were slowly added under stirring. The mixture was stirred for 45 min to allow the silica sol to fully adhere to the surface of the wollastonite. The mixture was then filtered, dried at 110°C for 1.5 h, and then heat-treated at 300°C for 1 h. After cooling, depolymerization, and sieving, silica sol-modified wollastonite was obtained.
[0040] Example 1 Preparation of fire-resistant sealing materials: S1. Add 100 parts of vinyl-terminated polydimethylsiloxane and 6 parts of borosilicate modifier prepared in Preparation Example 1 to a mixing device and mix at room temperature for 10 min. Then add 8 parts of fumed silica in batches, mixing for 10 min after each batch is added. Add the next batch only after the fumed silica is fully wetted. After the fumed silica is added, add 6 parts of modified wollastonite prepared in Preparation Example 2, 25 parts of aluminum hydroxide, 5 parts of zinc borate, 12 parts of mica powder, 8 parts of wollastonite and 10 parts of glass powder in sequence, mixing for 10 min after each filler is added. After all fillers are added, heat to 50°C and continue mixing for 40 min. Then degas under vacuum for 10 min under an absolute pressure of 5 kPa to obtain the base adhesive. S2. Divide the obtained base compound into two parts. Add 0.40 parts of Karstedt platinum catalyst to one part of the base compound and mix for 15 min to obtain the first component. Add 12 parts of hydrogen-containing MQ silicone resin and 0.06 parts of 1-ethynyl-1-cyclohexanol to the other part of the base compound and mix for 15 min to obtain the second component. S3. Mix all the obtained first and second components, mix at room temperature for 20 minutes, and then vacuum degas for 30 minutes under an absolute pressure of 5 kPa to obtain the adhesive to be cured; inject the adhesive to be cured into the mold, cure at 100°C for 30 minutes, and demold after cooling to room temperature to obtain the fireproof sealing material.
[0041] Example 2 Preparation of fire-resistant sealing materials: The preparation method is largely the same as in Example 1, except that the amount of borosilicate modifier obtained in Example 1 is increased from 6 parts to 8 parts, while the amount of other raw materials and preparation conditions are the same as in Example 1.
[0042] Comparative Example 1 Preparation of fire-resistant sealing materials: The preparation method is largely the same as in Example 1, except that 6 parts of the modified wollastonite obtained in Preparation Example 2 are not added, and the amount of ordinary wollastonite is increased from 8 parts to 14 parts. The amounts of other raw materials and preparation conditions are the same as in Example 1.
[0043] Comparative Example 2 Preparation of fire-resistant sealing materials: The preparation method is largely the same as in Example 1, except that 6 parts of the modified wollastonite obtained in Preparation Example 2 are not added, and the amount of ordinary wollastonite is increased from 8 parts to 14 parts. The amount of borosilicate modifier obtained in Preparation Example 1 is increased from 6 parts to 8 parts. The amounts of other raw materials and preparation conditions are the same as in Example 1.
[0044] Comparative Example 3 Preparation of fire-resistant sealing materials: The preparation method is largely the same as in Example 1, except that 6 parts of the modified wollastonite obtained in Preparation Example 2 are not added, and the amount of ordinary wollastonite is increased from 8 parts to 14 parts. The amount of borosilicate modifier obtained in Preparation Example 1 is increased from 6 parts to 10 parts. The amounts of other raw materials and preparation conditions are the same as in Example 1.
[0045] Comparative Example 4 Preparation of fire-resistant sealing materials: The preparation was largely the same as in Example 1, except that the borosilicate modifier obtained in Example 1 was not added. The amounts of other raw materials and preparation conditions were the same as in Example 1.
[0046] Comparative Example 5 Preparation of fire-resistant sealing materials: The preparation method is largely the same as Example 1, except that the borosilicate modifier obtained in Preparation Example 1 and 6 parts of the modified wollastonite obtained in Preparation Example 2 are not added, and the amount of ordinary wollastonite is increased from 8 parts to 14 parts. The amounts of other raw materials and preparation conditions are the same as in Example 1.
[0047] Comparative Example 6 Preparation of fire-resistant sealing materials: Similar to Example 1, except that instead of adding 6 parts of the modified wollastonite obtained in Preparation Example 2, 5.71 parts of ordinary wollastonite and 0.29 parts of nano-alumina were added, so that the actual amount of wollastonite and alumina used was basically the same as the amount of solid wollastonite and alumina used in the 6 parts of modified wollastonite obtained in Preparation Example 2. At the same time, the original 8 parts of ordinary wollastonite remained unchanged, and the amount of other raw materials and preparation conditions were the same as in Example 1.
[0048] Comparative Example 7 Preparation of fire-resistant sealing materials: The preparation was largely the same as in Example 1, except that 6 parts of the modified wollastonite obtained in Preparation Example 2 were replaced with 6 parts of the silica sol-modified wollastonite obtained in Comparative Preparation Example 2. The amounts of other raw materials and preparation conditions were the same as in Example 1.
[0049] Comparative Example 8 Preparation of fire-resistant sealing materials: The preparation was largely the same as in Example 1, except that 6 parts of the borosilicate modifier obtained in Preparation Example 1 were replaced with 6 parts of the borosilicate modifier without reactive vinyl groups obtained in Comparative Preparation Example 1. The amounts of other raw materials and preparation conditions were the same as in Example 1.
[0050] Test section Linear shrinkage after firing: Fireproof sealing materials from each example and comparative example were used to prepare samples with dimensions of 50mm×50mm×60mm. The length and width of the samples before heating were measured. The samples were placed at 1000℃ for 30 minutes and cooled to room temperature. The length and width of the samples were measured again to calculate the linear shrinkage after firing. The maximum crack width on the sample surface was measured using plug wires (0.1mm, 0.2mm, 0.3mm, 0.5mm, 1.0mm, 1.5mm, 2.5mm). The linear shrinkage after firing and the maximum crack width are used to reflect the dimensional stability and crack resistance of the material after being exposed to fire. Each group of samples was tested three times and the average value was taken. The test results are shown in Table 1.
[0051] Residual compressive strength after burning: The fireproof sealing materials of each embodiment and comparative example were made into cylindrical specimens with a diameter of 50 mm and a height of 50 mm. The specimens were placed at 1000℃ for 30 min and cooled to room temperature. The specimens were then placed at the center of the upper and lower pressure plates of the pressure testing machine without any padding between the specimens and the pressure plates. The load was continuously and uniformly applied until the residual specimens after burning were destroyed. The residual compressive strength after burning was obtained. The residual compressive strength after burning is used to reflect the load-bearing and supporting capacity of the material's residual structure after being exposed to fire. Each group of specimens was tested three times and the average value was taken. The test results are shown in Table 2.
[0052] Table 1
[0053] Table 2
[0054] Comparative Examples 1-3 show that, without the addition of modified wollastonite, while increasing the boron-containing high-temperature phase in the system further increases the amount of boron-containing softening phase, the excessive boron-containing softening phase tends to exhibit significant flow and sintering densification at high temperatures, causing the residual skeleton to undergo greater volume shrinkage while forming bonds. When the shrinkage exceeds the coordinated deformation capacity of the residual skeleton, localized inconsistent shrinkage and crack formation easily occur, thereby weakening the continuity and load-bearing capacity of the post-sintering residual structure. Therefore, simply increasing the boron-siloxane modifier cannot solve the problem of post-sintering structural stability; instead, it may lead to new shrinkage and cracking problems due to the excessive amount of high-temperature softening phase. This result indicates that further increases in the boron-siloxane modifier are limited by high-temperature sintering behavior, and it is necessary to introduce components that can stabilize the inorganic skeleton and regulate the boron-containing high-temperature phase to further exert its high-temperature bonding effect.
[0055] As can be seen from Example 1 and Comparative Example 1, with the same amount of borosilicate modifier, the introduction of wollastonite modified with alumina sol further reduces the post-firing shrinkage and cracking of the material, while improving the post-firing residual compressive strength. This may be because the wollastonite in the modified wollastonite can form a relatively stable inorganic framework at high temperatures. Its alumina-rich surface structure further regulates the softening and sintering process of the boron-containing high-temperature phase formed by borosilicate, thereby reducing excessive flow of the boron-containing softening phase and the resulting framework rearrangement and compaction shrinkage. This allows the binder phase formed by borosilicate to be used more for connecting and fixing the inorganic framework. Therefore, the modified wollastonite can maintain the high-temperature binding effect of borosilicate while reducing the shrinkage and cracking caused by excessive sintering, and further improve the integrity and load-bearing capacity of the post-firing residual structure.
[0056] Comparative Example 2 and Example 2 show that, with a borosilicate modifier dosage of 8 parts, the introduction of modified wollastonite improved the post-firing shrinkage and cracking of the material, and also enhanced the load-bearing capacity of the post-firing residual structure. This may be because, at higher borosilicate modifier dosages, modified wollastonite can regulate the boron-containing high-temperature phase formed upon heating, and utilizes its relatively stable inorganic framework to limit excessive flow and structural rearrangement caused by the high-temperature softening phase, thereby reducing shrinkage and cracking caused by over-sintering. Simultaneously, modified wollastonite can provide a stable framework for the high-temperature bonding phase formed by borosilicate, allowing the high-temperature bonding effect to be more focused on the connection and consolidation between residual framework components. Therefore, modified wollastonite can partially mitigate the negative impacts of increased borosilicate dosage.
[0057] As can be seen from Example 1 and Comparative Example 4, when the same amount of modified wollastonite is added, the addition of borosilicate modifier in Example 1 further reduces the degree of post-firing shrinkage and cracking, and significantly improves the residual compressive strength after firing. This indicates that modified wollastonite can mainly stabilize the post-firing inorganic framework, but relying solely on modified wollastonite, there is still a lack of sufficient high-temperature bonding and consolidation between particles; after adding borosilicate modifier, the boron-containing high-temperature phase formed can promote the bonding and consolidation between modified wollastonite and silicon-rich residues and other ceramicized fillers, allowing the originally relatively stable but insufficiently bonded inorganic framework to further form a complete post-firing structure.
[0058] As can be seen from Example 1 and Comparative Example 5, in the base system with the simultaneous addition of hydrogen-containing MQ silicone resin, the further simultaneous introduction of borosilicate modifier and modified wollastonite significantly suppressed post-firing shrinkage and cracking, and significantly improved the post-firing residual compressive strength. This indicates that although the hydrogen-containing MQ silicone resin in the base system can increase the post-firing residue, the residue still suffers from insufficient bonding and a loose structure. The addition of borosilicate modifier promotes high-temperature bonding and consolidation between the residue and the ceramicized filler, while the modified wollastonite further improves the stability of the inorganic framework and regulates the sintering process of the boron-containing high-temperature phase, resulting in a more complete post-firing structure. Therefore, the combined use of borosilicate modifier and modified wollastonite can further improve the post-firing structural stability and load-bearing capacity of the base system.
[0059] As can be seen from Example 1 and Comparative Example 6, when the amount of borosilicate modifier and other components are basically the same, replacing the modified wollastonite obtained by pre-modifying wollastonite with alumina sol with a direct blend of ordinary wollastonite and nano-alumina resulted in increased post-firing shrinkage and cracking, and decreased post-firing residual compressive strength. This indicates that alumina does not function solely through simple addition. Pre-adhering alumina sol to the wollastonite surface helps maintain a tighter bond between the alumina-rich components and the wollastonite framework, thereby more effectively regulating the sintering process of the boron-containing high-temperature phase formed by borosilicate and improving the stability of the post-firing framework. Therefore, the role of modified wollastonite in this application cannot be completely replaced by a simple blend of ordinary wollastonite and alumina.
[0060] As can be seen from Example 1 and Comparative Example 7, when the amount of borosilicate modifier and other components are basically the same, replacing the alumina sol-modified wollastonite with silica sol-modified wollastonite increases the post-firing shrinkage and cracking, and reduces the post-firing residual compressive strength. This indicates that sol modification of wollastonite does not always achieve the same effect. The surface layer formed by silica sol has limited effect on regulating the boron-containing high-temperature phase of borosilicate, while the aluminum-rich surface layer formed by alumina sol can more effectively improve the sintering and consolidation process between the boron-containing high-temperature phase and the inorganic framework, thereby making the post-firing structure more stable.
[0061] As can be seen from Example 1 and Comparative Example 8, when the modified wollastonite and other components are the same, replacing the borosilicate modifier containing reactive vinyl groups with a borosilicate modifier without reactive vinyl groups significantly increases the post-firing shrinkage and cracking, and significantly reduces the post-firing residual compressive strength. This indicates that the vinyl groups in the borosilicate modifier can participate in the hydrosilylation reaction of the hydrogen-containing MQ silicone resin, making the borosilicate modifier more stably bound in the cured network, thus facilitating its uniform high-temperature bonding and consolidation during firing. Without reactive vinyl groups, this effect is weakened, making it difficult to fully utilize the synergistic effect between the borosilicate modifier and the modified wollastonite.
[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A fireproof sealing material, characterized in that, The raw materials include the following parts by weight: 100 parts vinyl polysiloxane, 8-16 parts hydrogen-containing MQ silicone resin, 4-8 parts borosilicate modifier, 4-8 parts modified wollastonite, 20-35 parts flame retardant filler, 30-40 parts ceramicized filler, 6-12 parts reinforcing filler, 0.2-0.6 parts platinum catalyst and 0.05-0.1 parts inhibitor; The borosilicate modifier is prepared by a condensation reaction of hydroxyl-terminated polysiloxane, trialkyl borate, and vinylalkoxysilane. The modified wollastonite is obtained by modifying wollastonite with alumina sol.
2. The fireproof sealing material according to claim 1, characterized in that, The preparation method of the borosilicate modifier includes the following steps: 100 parts of hydroxyl-terminated polysiloxane, 4-10 parts of trialkyl borate, and 5-12 parts of vinylalkoxysilane were mixed and reacted at 70-90°C for 1.5-3 hours under anhydrous and nitrogen protection to induce a condensation reaction between the hydroxyl-terminated polysiloxane, trialkyl borate, and vinylalkoxysilane. Subsequently, the temperature was raised to 110-130°C and the reaction was continued for 1-2 hours under a pressure of 4-10 kPa. The low-molecular-weight substances generated in the reaction were removed to obtain a product containing polysiloxane segments, Si-OB structure, and vinyl groups, which was used as a borosilicate modifier.
3. The fireproof sealing material according to claim 2, characterized in that, The hydroxyl-terminated polysiloxane is a hydroxyl-terminated polydimethylsiloxane, and the viscosity of the hydroxyl-terminated polydimethylsiloxane at 25°C is 1000-2000 mPa·s. The trialkyl borate includes at least one of trimethyl borate, triethyl borate, and triisopropyl borate. The vinylalkoxysilane includes at least one of vinyltrimethoxysilane and vinyltriethoxysilane.
4. The fireproof sealing material according to claim 1, characterized in that, The method for preparing the modified wollastonite includes the following steps: 100 parts of wollastonite were dispersed in water, and 15-40 parts of alumina sol were added at 50-70°C with stirring. The mixture was continued for 30-60 minutes to allow the alumina sol to adhere to the surface of the wollastonite. The wollastonite was then dried at 100-120°C for 1-2 hours, followed by heat treatment at 250-350°C for 0.5-2 hours. After cooling, the wollastonite was sieved to obtain the modified wollastonite. The solid content of the alumina sol is 15-25 wt%.
5. The fireproof sealing material according to claim 1, characterized in that, The vinyl polysiloxane is a vinyl-terminated polydimethylsiloxane, which has a viscosity of 3000-8000 mPa·s at 25°C and a vinyl content of 0.20-0.50 wt%.
6. The fireproof sealing material according to claim 1, characterized in that, The hydrogen-containing MQ silicone resin has a molar ratio of M structural units to Q structural units of 0.7 to 1.1:1, a Si-H content of 0.10 to 0.3 wt%, and a number-average molecular weight of 2000 to 6000.
7. The fireproof sealing material according to claim 1, characterized in that, The flame-retardant filler is one or more of aluminum hydroxide, magnesium hydroxide, and zinc borate.
8. The fireproof sealing material according to claim 1, characterized in that, The ceramicized filler is one or more of mica powder, wollastonite and glass powder, and the reinforcing filler is at least one of fumed silica and precipitated silica.
9. A method for preparing a fireproof sealing material, characterized in that, Includes the following steps: S1. Providing the raw materials included in the fire-stopping material according to any one of claims 1 to 8; S2. Mix vinyl polysiloxane, borosilicate modifier, modified wollastonite, flame retardant filler, ceramicized filler and reinforcing filler evenly to obtain the base adhesive; S3. The base adhesive is divided into two parts. One part of the base adhesive is mixed with a platinum catalyst to obtain the first component. The other part of the base adhesive is mixed with hydrogen-containing MQ silicone resin and an inhibitor to obtain the second component. S4. The first component and the second component are mixed to allow the Si-H in the hydrogen-containing MQ silicone resin to undergo a hydrosilylation reaction with the vinyl polysiloxane and the vinyl in the borosilicate modifier, and the fireproof sealing material is obtained after curing.
10. The application of the fire-stopping material according to any one of claims 1 to 8 or the fire-stopping material prepared by the preparation method according to claim 9 in the preparation of fire-stopping modules.